PENERAPAN MODEL PEMBELAJARAN KOOPERATIF POE (Predict, Observe, Explain) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KESETIMBANGAN KIMIA DI KELAS XI MIA SMA MUHAMMADIYAH 1 PEKANBARU - Anasa, Fauziah; Resmiwetti, Resmiwetti; M Noer, Asmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The research about implementation to improve student learning achievement on the subject chemical equilibrium at the class XI MIA SMA Muhammadiyah 1 Pekanbaru. The research was a form of experimental research with the design Randomized Control Group Pretest-Posttest. The sample consists of two classes, class XI MIA 5 as the experimental class and class XI MIA 3 as the control class is determined randomly after normality test and homogeneity test. Experimental class was implied of learning model cooperative POE (Predict, Observe, Explain) while the control class didn’t imply learning model cooperative POE (Predict, Observe, Explain). Data analysis technique used is the t-test. Based on the results of data processing obtained tcount > ttable is 3,38 > 2,00, its means that the implementation of learning model cooperative POE (Predict, Observe, Explain) can improve students learning achievement on the subject chemical equilibrium at the class XI MIA SMA Muhammadiyah 1 pekanbaru. Categories of learning achievement of student amount 0,78 with the high categories.Keywords : Learning Model POE (Predict, Observe, Explain), Learning Achievement, Chemical Equilibrium